Representasi Pengetahuan Produk Sampo Melalui Model Ontologi Sebagai Dasar Sistem Rekomendasi - Ni Kadek Risma Yudyadnyani; I Gede Santi Astawa (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2026)
Shampoo is one of the most commonly used hair care products, offering various formulations tailored to specific hair and scalp needs. However, users often face challenges in selecting suitable products, especially when dealing with individual conditions such as dandruff, hair loss, or sensitive scalp. This research aims to develop a domain ontology that models knowledge about shampoo products using the Methontology methodology. The ontology was built using Protégé software and consists of 6 main classes, 9 object properties, 3 data properties, and 48 individuals. It represents key aspects such as product brand, active ingredients, usage effects, hair types, and potential incompatibilities. Evaluation was conducted through SPARQL queries to test the accuracy and usefulness of the ontology in supporting semantic search and personalized recommendations. The results demonstrate that the ontology effectively captures relevant knowledge and can serve as a foundation for intelligent recommendation systems, helping users find appropriate shampoo products based on their needs.